A force of 2 pounds stretches a spring 1 foot. A mass weighing 3.2 pounds is attached to the spring, and the system is then immersed in a medium that offers a damping force that is numerically equal to 0.4 times the instantaneous velocity.

(a.) Find the equation of motion if the mass is initially released from rest from a
point 1 foot above the equilibrium position.

(b.) Find the first time at which the mass passes through the equilibrium position
heading upwards.

Respuesta :

Answer:

[tex]x(t) = e^-2t(c_1cos4t+c_2cos4t)[/tex]

[tex]x(t) = \sqrt{5}/2* e^-2tsin(4t+4.24)[/tex]

t =1.294

Explanation:

Let m be the mass attached, let k be the spring constant and let p be the positive damping constant. The Newton's second law for the system is

[tex]md^2x/dt^2 = -kx-\beta dx/dt[/tex]

where x(t) is the displacement from the equilibrium position. The equation can be transformed into  

 [tex]d^2x/dt^2 +\beta /m*(dx/dt)+k/m*x=0[/tex]

(a) Let's determine the equation of motion. We must convert units of weight into units of mass  

[tex]m=W/g = 3.2/32 =1/10 slug[/tex]

From Hooke's law we can calculate the spring constant k.  

[tex]k = W/s = 2/1 = 2lb/ft[/tex]

If we put m = 1/10 slugs, k = 2 lb/ft and [tex]\beta[/tex] = 0.4 into the DE, we get

 [tex]d^2x/dt^2 +4*(dx/dt)+20*x=0[/tex]

The auxiliary equation is m^2+4*m+20 = 0 and its solutions are m_1 = -2-4_i and m_2 = -2 + 4i. The general solution is then  

[tex]x(t) = e^-2t(c_1cos4t+c_2cos4t)[/tex]

From the initial conditions

[tex]x(0) = -1ft , x'(0) = 0ft/s[/tex]

we can find the equation of motion  

[tex]x(t) = e^-2t(-cos4t-1/2sin4t)[/tex]

(b) We need to express the equation of motion in the alternative form

first attachment

The amplitude is  

[tex]A=\sqrt{c_1^2+c_2^2}=\sqrt{(-1)^2+(-1/2)^2}= \sqrt{5}/2[/tex]

and the phase angle is

sin∅=[tex]c_1/A=-2/\sqrt{5}[/tex]

cos∅=[tex]c_2/A=-1/\sqrt{5}[/tex]

tan∅=2

∅=[tex]\pi +tan^-1*2[/tex]

 =4.24

[tex]x(t) = \sqrt{5}/2* e^-2tsin(4t+4.24)[/tex]

(c) lb find the wanted time, we will need the derivative of the equation of motion  

x'(t)=[tex]5*e^-2tsin4t[/tex]

The mass passes through the equilibrium when  

x(t) =0

[tex]e^-2t(-cos4t-1/2sin4t)=0\\-cos4t-1/2sin4t=0\\tan4t=-2\\4t=-tan^-1+k\pi[/tex]

t =-0.2786+k[tex]\pi[/tex]/4

The velocity at those times is  

second attachment

The first (positive) time at which the mass passes through the equilibrium heading upward is for k = 2 (when x' < 0).  

t =1.294

Ver imagen Hashirriaz830
Ver imagen Hashirriaz830